2007
DOI: 10.1007/s00234-007-0262-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative morphologic evaluation of magnetic resonance imaging during and after treatment of childhood leukemia

Abstract: Introduction-Medical advances over the last several decades, including CNS prophylaxis, have greatly increased survival in children with leukemia. As survival rates have increased, clinicians and scientists have been afforded the opportunity to further develop treatments to improve the quality of life of survivors by minimizing the long-term adverse effects. When evaluating the effect of antileukemia therapy on the developing brain, magnetic resonance (MR) imaging has been the preferred modality because it qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 93 publications
(139 reference statements)
1
13
0
1
Order By: Relevance
“…The greater susceptibility of visual-auditory learning to disruption may help explain findings of greater risk for reading deficits among children with localized ependymoma after CRT. The increased vulnerability of younger children to late effects has been suggested in the literature, with one explanation being that younger children experience greater loss of white matter volume following irradiation compared to older children 37-40. It has also been suggested that visual memory may be disproportionately affected following white matter injury early in life, particularly as the right hemisphere may contain greater volume of white matter 41-44.…”
Section: Discussionmentioning
confidence: 99%
“…The greater susceptibility of visual-auditory learning to disruption may help explain findings of greater risk for reading deficits among children with localized ependymoma after CRT. The increased vulnerability of younger children to late effects has been suggested in the literature, with one explanation being that younger children experience greater loss of white matter volume following irradiation compared to older children 37-40. It has also been suggested that visual memory may be disproportionately affected following white matter injury early in life, particularly as the right hemisphere may contain greater volume of white matter 41-44.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Reddick et al (6) included a VBA analysis of patients during therapy for ALL stratified by age at diagnosis but did not control for treatment arm (intensity of therapy) which is highly correlated with age at diagnosis. In the current longitudinal study, all 197 subjects are used in the VBA and treatment arm is included as a covariate thus increasing the power of the study and resulting in increased statistical significance as demonstrated by the p-values achieved.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that increasing intensity of therapy, corresponding to more courses and higher doses of IV-MTX, was associated with an increased prevalence, intensity and extent of LE. Most of the LE was transient but the impact of these changes on the developing brain are unknown (6). …”
Section: Introductionmentioning
confidence: 99%
“…Prior reports have noted that in MTX-induced leukoencephalopathy diffusion, restriction appears simultaneously with symptom onset but before any white matter changes on e20 | www.jpho-online.com T2-weighted images. 10,11 However, isolated T2 hyperintensity is a finding in early-delayed radiation toxicity. 12 Ring-enhancing lesions are common MRI findings in CNS infection but are not seen in MTX-induced leukoencephalopathy.…”
Section: Discussionmentioning
confidence: 99%